Bookkeeping, And Financial Reporting System On E-Mobil Parts - Widijaya Widijaya; Riskiyanto Riskiyanto (ConCEPt - Conference on Community Engagement Project, 2023)
The purpose of this study is to design an accounting system for E-Mobil Parts owners. E-Mobil Parts is an online spare part shop on at online platform. E-Mobil Parts has been operating for 6 years and manually bookkeeping the accounting records. The manual bookkeeping causes ineffective and inefficient for E-Mobil Part for preparing the financial report. To retrieve the information needed for the design of the Microsoft Access-based accounting system the author conducted observation and interviews. The author will decide on the needs of E-Mobil Parts and create an account list form, customer list form, vendor list form, inventory list form, purchase form, and sales form and reports for the owner of E-Mobil Parts such as income statement, statement of owner equity financial position, cash flow statement, purchase report, sales report, inventory report, payable report, receivable report, and ledger report. The implementation of the accounting system for E-Mobil Parts will run properly and minimize errors.